2023
DOI: 10.1002/jtr.2571
|View full text |Cite
|
Sign up to set email alerts
|

Residents as gratuitous referrals at destination: An integrative model from altruistic values to pro‐tourism behavior

Abstract: The altruistically shared information provided by residents is significant for travelers, affecting decisions they postpone until arrival at their destination. This study integrates altruism as a personal value with the basic postulates of social exchange theory and theory of reasoned action to explain the behavior of residents in terms of gratuitous referrals at destination (GRAD). A structural equation model is tested at a tourist destination on the coast of southwestern Spain. The results reveal that the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(186 reference statements)
2
3
0
Order By: Relevance
“…Residents perceived positive tourism impacts as significant determinants of their attitudes toward tourists (H1) and about tourism (H2). These results are similar to previous findings [14,19,23,25,26] and supported through SET. For example, Martin et al [25] found that both residents' attitudes concerning tourists and tourism overall were positively influenced by perceived positive tourism impacts.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Residents perceived positive tourism impacts as significant determinants of their attitudes toward tourists (H1) and about tourism (H2). These results are similar to previous findings [14,19,23,25,26] and supported through SET. For example, Martin et al [25] found that both residents' attitudes concerning tourists and tourism overall were positively influenced by perceived positive tourism impacts.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study, Nugroho and Numata [24] investigated the relationship between residents' perceptions of tourism and their supportive attitudes, employing the SET framework. Their results revealed that residents who perceived tourism as beneficial were more likely to express support, consistent with earlier research findings [14,18]. Additionally, Nugroho and Numata [24] identified a negative association between residents' supportive attitudes toward community-based tourism development in Indonesia and their perceived costs.…”
Section: The Positive Impacts Of Tourism and Social Exchange Theory (...supporting
confidence: 77%
See 3 more Smart Citations